The Impact of Corporate Social Responsibility on Total Factor Productivity - Sheng, Tianqi (Transactions on Social Science, Education and Humanities Research, 2024)
With the advent of globalization, modern enterprises, as crucial pillars of socio-economic development, directly influence their own economic benefits and societal stability. In an increasingly competitive market, enterprises should not only pursue the maximization of economic benefits but also fulfill their social responsibilities, thereby shaping a positive social impact and gaining wide recognition across various sectors. Thus, the concept of corporate social responsibility has emerged, becoming an indispensable part of corporate development strategies. Concurrently, total factor productivity, as a key indicator of enterprise production efficiency, is crucial for long-term development. Improvements in total factor productivity not only enhance a company’s competitiveness but also drive overall socio-economic progress. Therefore, exploring the impact of corporate social responsibility on total factor productivity not only helps to understand the intrinsic connection between the two but also provides strong theoretical support and practical guidance for achieving sustainable development.